Relevansi Pemikiran Al-Ghazali tentang Tasawuf dalam Pembentukan Karakter Islami Generasi Milenial - Agus Ardiana; Ahmad Husaini; Mokhamad Farhan F; Dede Nurzaman (Moral : Jurnal kajian Pendidikan Islam, 2026)
This study examines the relevance of Al-Ghazali’s Sufi thought as articulated in his monumental work Ihya Ulumuddin to the cultivation of Islamic character among the millennial generation in the digital era. The rapid development of technology, globalization, and changing social values have created significant challenges for young Muslims, including moral degradation, identity crises, and weakened spiritual awareness. Employing a library research method with a qualitative-descriptive approach, this study analyzes the fundamental concepts of Al-Ghazali’s Sufism, including tazkiyatun nafs (purification of the soul), maqamat (spiritual stages), akhlaqul karimah (noble character), and the process of spiritual discipline as a means of achieving human perfection. The study explores how these concepts can be contextualized within contemporary Islamic education to address the moral and spiritual challenges faced by the millennial generation. The findings indicate that Al-Ghazali’s Sufi thought remains highly relevant and adaptable as a framework for character formation by emphasizing self-reflection, ethical responsibility, emotional control, and closeness to Allah. Furthermore, the integration of Sufi values in educational practices can strengthen religious identity, social awareness, and moral resilience among young Muslims. Therefore, Al-Ghazali’s perspective provides a comprehensive foundation for developing Islamic character education that is responsive to the demands of the modern digital era while maintaining essential spiritual values.